Optimal sizing and performance assessment of stand-alone PV systems using optimum hybrid sizing strategy - Mohamad Abed; Amarendra Reddy B; T.R. Jyothsna; Nabil Mohammed (Results in Engineering)
A hybrid strategy for the optimal sizing of stand-alone photovoltaic systems (SAPVS) is proposed in this article, with an emphasis on the worst-case photovoltaic (PV) power generation scenario. Since individual optimization methods for SAPVS sizing aim to address multipurpose challenges, the hybrid approach effectively manages such complexities. This strategy is developed by integrating three stages. These are (i) Initial exploration stage, (ii) Implementation of integrated calculation methods, and (iii) Rigorous performance assessment of the designed system. The initial exploration stage provides a preliminary understanding to determine the worst-case PV power generation at a predetermined installation location. In this stage, data are obtained from the Global Solar Atlas (GSA) platform and PVsyst software reports, and critical parameters such as Peak Sun Hour (PSH), designing month, annual optimal tilt, and azimuth angles are defined. In the Implementation of integrated calculation methods, intuitive and numerical calculation methods are integrated into the methodology, supported by a feedback-closed loop for iterative refinement and comparison. In the performance assessment stage, the designed SAPVS undergoes a rigorous performance evaluation to ensure compliance with technical requirements before the practical implementation on the site. Detailed system component simulations, including electro-magnetic transients (EMT) in MATLAB/Simulink and PVsyst, are employed. The performance assessment utilizes real-time data for December, identified as the worst-case month for PV power generation in the initial exploration stage. Actual data for a residential load in Latakia, Syria, are used to validate the design. The preliminary exploration stage significantly accelerates the performance assessment. For instance, EMT simulations in MATLAB/Simulink require one day to complete a single case (December). Without the exploration stage, simulations for all 12 months would exceed 12 days. Results confirm that the designed SAPVS meets technical requirements, with steady-state and dynamic performances assessed through graphical analyses of electrical characteristics, power flow, and output curves.